2015
DOI: 10.1515/eces-2014-0048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fertilization on Microbial Activities, Soil Hydrophobicity and Mineral Nitrogen Leaching

Abstract: This work presents the analysis of the influence of compost and reclamation substrate addition and mineral fertilizers application on leaching of mineral nitrogen, microbial activities, soil hydrophobicity and plant biomass production. To demonstrate the effect of compost, reclamation substrate and mineral nitrogen (Nmin) addition on above parameters, the pot experiment was performed. As a model crop, Deschampsia caespitosa L. was used and cultivated for 63 days in climate chamber. The leaching of Nmjn was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…The 16S rDNA AOB value is an indicator of microbial activity in the process of nitrogen mineralization. It has been observed that the addition of organic fertilizers (e.g., compost) positively affects the microbial activity and utilization of nitrogen in contrast to the addition of the NPK fertilizer [104,105]. Among all the treatments, manure amendment with biochar shows the highest log 16S rDNA AOB copies.…”
Section: S Rdna (Aob)mentioning
confidence: 99%
“…The 16S rDNA AOB value is an indicator of microbial activity in the process of nitrogen mineralization. It has been observed that the addition of organic fertilizers (e.g., compost) positively affects the microbial activity and utilization of nitrogen in contrast to the addition of the NPK fertilizer [104,105]. Among all the treatments, manure amendment with biochar shows the highest log 16S rDNA AOB copies.…”
Section: S Rdna (Aob)mentioning
confidence: 99%
“…For this reason, soil water retention can be easily influenced by changes in soil organic matter, which can be initiated, e.g. by land management (Weber et al, 2007;Ulyett et al, 2014;Elbl et al, 2015;Hagemann et al, 2017) or climate change (Rawls et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…3: 95-101 Plant Soil Environ. amount was close to the MF rate, but produced 32% higher grain N, due to the combination of a more constant release of N throughout the growth cycle, and the improvement of soil physical properties, primarily porosity (Kępka et al 2016). The beneficial effects of biosolids application on the growth and N uptake of spring barley may also be attributed to the supply of micronutrients (Esperschuetz et al 2016a), and to the improvement of soil biological activity (Elbl et al 2014, Plošek et al 2017. Thus, biosolids provide more benefits than mineral fertilisers, especially in semiarid conditions and in soils that are low in organic matter, which is a common feature in the Mediterranean region (Antolin et al 2005, Antoniadis et al 2015.…”
mentioning
confidence: 99%